Detecting Individual Intentional Behavior In Committing Financial Report Fraud Using The Theory Of Planned Behavior - Anggi Yodhita (Journal Research of Social Science, Economics, and Management, 2023)
This study aims to identify, analyze, and provide empirical evidence on the influence of attitude, subjective norms, and perceived behavioral control on the individual's intention to engage in financial reporting fraud among civil servants in the Ministry of Finance in Jakarta, Indonesia. The research utilizes a survey method for data collection, with the target population being civil servants working in the Ministry of Finance in Indonesia. The sample size for this study is 120 respondents. Purposive sampling technique is employed for sample selection, and the data is analyzed using multiple linear regression analysis. Data is collected through a questionnaire. The findings of the study indicate that attitude does not have a significant influence on the intention to engage in financial fraud, while intention does not have an impact on actual fraudulent behavior. However, subjective norms and perceived behavioral control show a significant influence on the intention to commit financial reporting fraud.